2004
DOI: 10.1002/mas.10081
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of intact protein complexes by mass spectrometry

Abstract: I. Introduction 00   II. Electrospray Ionization of Biomacromolecules 00   III. Mass Analyzers for Biomacromolecular Mass Spectrometry 00 A.  Collisional Cooling and/or Focusing 00 B.  Alternative Mass Analyzers 00  IV. Solution‐Phase Properties of Proteins Complexes 00 A.  Protein–Protein Interactions 00 B.  Cooperativity and Cofactors 00 C.  Dynamics of Assembly 00   V. Gas‐Phase Properties of Protein Complexes 00 A.  Tandem Mass Spectrometry 00 B.  Charge Separation in Protein D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
559
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(589 citation statements)
references
References 127 publications
24
559
0
6
Order By: Relevance
“…Peaks from enzyme (E) and complex (EI) are seen. A narrow distribution of charge states from ϩ9 to ϩ12, with ϩ10 being the most intense, is formed as expected°for°the°protein°in°its°native°conformation° [25,30].°The°peaks°of°the°complex°(EI)°are°30°to°40%°as intense as those of the enzyme (E) for the same charge state, even though, from the solution K i , it is calculated that°almost°all°the°enzyme°was°in°the°complexed°form. The gas-phase abundances do not reflect the solution equilibria.…”
Section: Mass Spectramentioning
confidence: 58%
“…Peaks from enzyme (E) and complex (EI) are seen. A narrow distribution of charge states from ϩ9 to ϩ12, with ϩ10 being the most intense, is formed as expected°for°the°protein°in°its°native°conformation° [25,30].°The°peaks°of°the°complex°(EI)°are°30°to°40%°as intense as those of the enzyme (E) for the same charge state, even though, from the solution K i , it is calculated that°almost°all°the°enzyme°was°in°the°complexed°form. The gas-phase abundances do not reflect the solution equilibria.…”
Section: Mass Spectramentioning
confidence: 58%
“…Native MS allowed simultaneous detection of monomeric, dimeric and unfolded forms of cyt-c¢ and was therefore able to monitor the CO-induced monomerization of cyt-c¢. MS also allowed the detection of the CO-bound form of cyt-c¢, which to our knowledge is the first time that the binding of a gaseous ligand to a protein has been observed with MS. An explanation for the partial preservation of the CO-bound complex is that the bound CO molecule is located deep inside the channel that gives access to the distal coordination site [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in MS instrumentation have enabled the characterization of native, folded proteins and large protein complexes that are held together by weak noncovalent interactions [25,26]. Several studies have reported the use of this so-called native MS to study protein folding and cofactor binding [26,27].…”
Section: Monitoring Ligand-induced Monomerization Using Native Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NMR is limited to molecules with molecular weight not exceeding 40 kDa; furthermore, not all proteins are easy to crystallize for X-ray crystallography detection [26]. Electrospray ionization mass spectrometry (ESI-MS) has recently emerged as an attractive alternative [27][28][29][30][31]. Although unable to provide direct structural data as NMR and X-ray crystallography, ESI-MS does provide important stoichiometry information of the complex formed between two binding partners.…”
Section: T He Root Of Salvia Miltiorrhiza Is Known In China Asmentioning
confidence: 99%